Analisis Fisik dan Mekanik pada Pengembangan Panel Komposit Limbah Serbuk Kayu - Siswanti Zuraida; Sastita Pratiwi (JOURNAL OF APPLIED SCIENCE (JAPPS), 2020)
This research discusses about comparison, testing, and analyzing composite materials for develop the building panels for lightweigh-wall applications made from wood-industrial waste materials. Wood sawdust is used as a composite cement mixture as a binder of all materials with the mixture 0%, 5%, 10%, 15%, and 20% of total weight. This research uses quantitative methods with blocks as a sample sizes 10cm x 3cm x 1cm. The test includes flexible test, porosity test, and composite walldensity test to find out mechanical and physical properties of composite material. The result of this research shows that the usage of wood sawdust as a mixture for making composite panel with 0.4 water-factor at 28 days-age get the optimum value at 15% of mixture variation with flexibility of 7.18 MPa, density 1.61 kg/m³ and compressive strength of 58.42, MPa. These results indicate that the wall panel meets the requirement of SNI 03-0349-1989 with concrete steel-brick level IV as a non-structural brick. Based on these results, it can be concluded that composite panel can be used on the wall as an effort to reduce the impact of the ruins of the building, and reduce the danger as a disaster mitigation effort.